CIC break‐apart fluorescence in‐situ hybridization misses a subset of CIC–DUX4 sarcomas: a clinicopathological and molecular study. Issue 3 (5th July 2017) - Yoshida, Akihiko; Arai, Yasuhito; Kobayashi, Eisuke; Yonemori, Kan; Ogura, Koichi; Hama, Natsuko; Mukai, Wakako; Motoi, Toru; Kawai, Akira; Shibata, Tatsuhiro; Hiraoka, Nobuyoshi
Abstract : Aims: Approximately 60–70% of high‐grade round‐cell sarcomas that lack the Ewing sarcoma breakpoint region 1 ( EWSR1 ) rearrangement harbour a rearrangement of the CIC gene, most commonly CIC–DUX4 . Recent studies have established that CIC ‐rearranged sarcomas constitute a distinct group characterized by recognizable histology and immunoprofiles, such as positivity for ETV4 and WT1 and negativity for NKX2.2. Although these sarcomas are diagnosed increasingly in practice by fluorescence in‐situ hybridization (FISH) with CIC break‐apart probes, the optimal modality to diagnose these sarcomas has not been determined. In this study, we describe four round‐cell sarcomas that showed false‐negative results by CIC break‐apart FISH assays. Methods and results: These sarcomas showed characteristic histology of CIC ‐rearranged sarcomas, and all were immunohistochemically positive for ETV4 and WT1 and negative for NKX2.2. Although FISH showed non‐atypical negative signals for CIC rearrangement, high‐throughput RNA sequencing identified CIC–DUX4 and its fusion breakpoint in all cases. Their clinical and histological findings, as well as fusion points determined by RNA sequencing, did not differ significantly from those of nine FISH‐positive CIC–DUX4 sarcoma cases. We estimated that the FISH false‐negative rate for CIC ‐rearranged sarcomas was 14%. Although neither histology nor immunoprofiles (e.g. ETV4 and WT1) are entirely sensitive or specific for CIC ‐rearranged sarcomas, the observation that these four cases were identified successfully by such phenotypes suggested their practical utility. Conclusions: CIC break‐apart FISH assays missed a significant minority of CIC–DUX4 sarcomas, and full awareness of typical morphology and judicious immunohistochemical work‐ups, including analyses of ETV4 and WT1, should complement diagnostic assessment.